Encyclopedia of herbal medicine - Chevallier, Andrew (DK/Penguin Random House, 2016)
Newly revised and updated, the "Encyclopedia of herbal medicine" is the definitive reference on herbal plants and their medicinal properties for those seeking natural remedies. Detailed descriptions, constituents, and uses for over 550 plants. Practical how-to remedies for more than 80 ailments, ranging from headaches to arthritis. Includes the latest scientific research and safety advice.